Assessing the impact of climate change on land-falling tropical cyclones (LFTCs) over the North Indian Ocean (NIO) and their effects on coastal agriculture in Maharashtra: A case study - Shahenaz Mulla; Sudhir Kumar Singh; Rizwan Ahmed (Tropical Cyclone Research and Review)
The intensity of tropical cyclonic storms formed over the North Indian Ocean (NIO) has increased over the last two decades. The increasing severity of cyclonic storms has serious socioeconomic and agricultural consequences. Many people are concerned about the impact of global warming caused by climate change on extreme weather events, such as the frequency and intensity of Tropical Cyclones (TCs) that form over global ocean basins. High-intensity cyclones have become more common in the NIO, posing significant risks and vulnerability to coastal communities.The World Meteorological Organization (WMO) reported that the warmest year was 2015–21, and the warmest decade was 2011–2020, which could be attributed to increased levels of greenhouse gases. However, few studies on the impact of climate change on various characteristics of Land-falling Tropical Cyclones (LFTCs) between 2001 and 2021 have been conducted. As a result, we performed an analysis to evaluate the impact of climate change on various characteristics of LFTCs, such as TC patterns, eye scenes, over land duration, Land-falling intensity (LFI) of LFTCs formed between the years 2000 and 2021. TCs formed over the NIO (2001–2021) crossed the coast with higher LFI and have shown a significant increasing trend in current intensity. Furthermore, more overland duration, eye-pattern TCs, and eye scenes were observed between 2000 and 2021.This study also assessed the impact of Severe Cyclonic Storm (SCS) Nisarga on coastal agriculture of Maharashtra in terms of vegetation, and shoreline dynamics. The Nisarga’s landfall caused huge socioeconomic as well as agricultural damages including torrential rainfall, storm surges, and saltwater intrusion, causing biodiversity loss and prolonged soil degradation. Normalized differential vegetation index (NDVI) and Enhanced Vegetation Index (EVI) indices revealed a sharp decline in vegetation health during post-cyclone with slow recovery in the subsequent months. The findings of this study could be used to improve the accuracy of operational forecasting of TCs over the North Indian Ocean basins. The results also highlight the need for targeted coastal management, including mangrove restoration and adaptive agricultural strategies, to enhance resilience against future LFTCs.